1991
DOI: 10.1007/bf00314650
|View full text |Cite
|
Sign up to set email alerts
|

Two cases of cerebral toxoplasmosis in AIDS patients mimicking HIV-related dementia

Abstract: Two unusual cases of cerebral toxoplasmosis in AIDS patients are presented. Two homosexual males aged 33 and 52 years in CDC stage IV C1 complained of memory loss during the past 6 months, as well as weight loss and mild fever. They showed severe intellectual deterioration and discrete basal ganglia dysfunction. Motor performance and cognitive function as well as the conventional EEG findings were grossly abnormal. MRI was normal in the younger patient but showed signal-intensive zones in the basal ganglia and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

1993
1993
2020
2020

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…Infection is found throughout the world in the tissues of food animals [2]. While infection with T. gondii has generally thought to be primarily asymptomatic in immune competent humans, recent studies have suggested that infection may contribute to the development of various neurological and psychiatric symptoms [3-10] and that negative outcomes resulting from initial or chronic infection may be under-diagnosed [10-13]. These studies in humans are, however, associative and cannot prove if infection causes the behavior or the behavior increases the risk of infection.…”
Section: Introductionmentioning
confidence: 99%
“…Infection is found throughout the world in the tissues of food animals [2]. While infection with T. gondii has generally thought to be primarily asymptomatic in immune competent humans, recent studies have suggested that infection may contribute to the development of various neurological and psychiatric symptoms [3-10] and that negative outcomes resulting from initial or chronic infection may be under-diagnosed [10-13]. These studies in humans are, however, associative and cannot prove if infection causes the behavior or the behavior increases the risk of infection.…”
Section: Introductionmentioning
confidence: 99%
“…The effects of the lesions caused by these CNS-OIs on neurobehavioral functioning varies widely. CM has been associated with mania (Johannessen & Wilson, 1988), TE has been found to mimic HIV-associated dementia (Arendt et al, 1991) and to be associated with alexia (Luscher & Horber, 1992), and PML has been associated with integrative agnosia (Butter & Trobe, 1994). Thus, these conditions can result in focal or generalized neuropsychological abnormalities, as well as alterations in psychiatric functioning.…”
mentioning
confidence: 99%
“…Uncommonly, patients may present with an encephalitic illness rather than discrete brain abscesses. These individuals may present with fever, meningeal signs, such as headache, stiff neck and photophobia, and encephalopathy that is rapidly fatal (161,162). Similar clinical manifestations and course have been reported in people with necrotizing ventriculitis due to T. gondii (163).…”
Section: Clinical Featuresmentioning
confidence: 67%